Kinetic simulations underestimate the effects of waves during magnetic reconnection - J. Ng; J. Yoo; L.-J. Chen; N. Bessho; H. Ji (Physical Review Research)
Collisionless plasma systems are often studied using fully kinetic simulations, where protons and electrons are treated as particles. Due to their computational expense, it is necessary to reduce the ion-to-electron mass ratio m_{i}/m_{e} or the ratio between plasma and cyclotron frequencies in simulations of large systems. In this Letter we show that when electron-scale waves are present in larger-scale systems, numerical parameters affect their amplitudes and effects on the larger system. Using lower-hybrid drift waves during magnetic reconnection as an example, we find that the ratio between the wave electric field and the reconnection electric field scales as sqrt[m_{i}/m_{e}], while the phase relationship is also affected. The combination of these effects means that the anomalous drag that contributes to momentum balance in the reconnection region can be underestimated by an order of magnitude. The results are relevant to the coupling of electron-scale waves to ion-scale reconnection regions, and other systems such as collisionless shocks.